2016
DOI: 10.3168/jds.2016-11057
|View full text |Cite
|
Sign up to set email alerts
|

Identifying management and disease priorities of Canadian dairy industry stakeholders

Abstract: The objective of this study was to identify the key management and disease issues affecting the Canadian dairy industry. An online questionnaire (FluidSurveys, http://fluidsurveys.com/) was conducted between March 1 and May 31, 2014. A total of 1,025 responses were received from across Canada of which 68% (n=698) of respondents were dairy producers, and the remaining respondents represented veterinarians, university researchers, government personnel, and other allied industries. Participants were asked to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 7 publications
1
32
0
2
Order By: Relevance
“…This study consisted of 2 phases, the first of which was a questionnaire offered to all Canadian dairy producers between March 1 and April 30, 2015. The focus of the questionnaire was derived from a priority assessment of Canadian dairy industry stakeholders conducted in 2014 (Bauman et al, 2016). Before implementation, the questionnaire was given to an advisory group specific to the project, consisting of dairy producers, industry representatives, and veterinarians, which included representation from all provinces (Bauman et al, 2018).…”
Section: Survey Design and Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…This study consisted of 2 phases, the first of which was a questionnaire offered to all Canadian dairy producers between March 1 and April 30, 2015. The focus of the questionnaire was derived from a priority assessment of Canadian dairy industry stakeholders conducted in 2014 (Bauman et al, 2016). Before implementation, the questionnaire was given to an advisory group specific to the project, consisting of dairy producers, industry representatives, and veterinarians, which included representation from all provinces (Bauman et al, 2018).…”
Section: Survey Design and Administrationmentioning
confidence: 99%
“…The first Canadian National Dairy Study was designed based on identified management and disease priorities of Canadian dairy industry stakeholders (Bauman et al, 2016), and collected data from farms in all provinces regardless of enrollment in milk recording (Belage et al, 2017). This information has facilitated benchmarking of management practices, similar to the National Animal Health Monitoring System (NAHMS) in the United States (USDA-APHIS, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Data were obtained through a cross-sectional survey of the Canadian dairy cattle industry in the form of a comprehensive questionnaire (Bauman et al, 2016). The questionnaire was accessible from March 1 to April 30, 2015, and all licensed dairy producers received a mailed letter of invitation to participate.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…The questionnaire was designed in response to a needs assessment conducted in 2014 involving Canadian dairy industry stakeholders (Bauman et al, 2016). Collaborators from the University of Guelph (Guelph, Ontario, Canada), University of Saskatchewan (Saskatoon, Saskatchewan, Canada), University of Calgary (Calgary, Alberta, Canada), Université de Montréal (St. Hyacinthe, Quebec, Canada), and University of Prince Edward Island (Charlottetown, Prince Edward Island, Canada) formulated questions focused on the 5 main management and disease priorities.…”
Section: Questionnaire Designmentioning
confidence: 99%
See 1 more Smart Citation